Rice responds to endophytic colonization which is independent of the common symbiotic signaling pathway - Chen, Xi; Miché, Lucie; Sachs, Sabrina; Wang, Qi; Buschart, Anna; Yang, Haiyuan; Vera Cruz, Casiana M.; Hurek, Thomas; Reinhold-Hurek, Barbara (Wiley, 2015)
As molecular interactions of plants with N2‐fixing endophytes are largely uncharacterized, we investigated whether the common signaling pathway (CSP) shared by root nodule symbioses (RNS) and arbuscular mycorrhizal (AM) symbioses may have been recruited for the endophytic Azoarcus sp.–rice (Oryza sativa) interaction, and combined this investigation with global approaches to characterize rice root responses to endophytic colonization. Putative homologs of genes required for the CSP were analyzed for their putative role in endophytic colonization. Proteomic and suppressive subtractive hybridization (SSH) approaches were also applied, and a comparison of defense‐related processes was carried out by setting up a pathosystem for flooded roots with Xanthomonas oryzae pv. oryzae strain PXO99 (Xoo). All tested genes were expressed in rice roots seedlings but not induced upon Azoarcus sp. inoculation, and the oscyclops and oscastor mutants were not impaired in endophytic colonization. Global approaches highlighted changes in rice metabolic activity and Ca2+‐dependent signaling in roots colonized by endophytes, including some stress proteins. Marker genes for defense responses were induced to a lesser extent by the endophytes than by the pathogen, indicating a more compatible interaction. Our results thus suggest that rice roots respond to endophytic colonization by inducing metabolic shifts and signaling events, for which the CSP is not essential.As molecular interactions of plants with N2‐fixing endophytes are largely uncharacterized, we investigated whether the common signaling pathway (CSP) shared by root nodule symbioses (RNS) and arbuscular mycorrhizal (AM) symbioses may have been recruited for the endophytic Azoarcus sp.–rice (Oryza sativa) interaction, and combined this investigation with global approaches to characterize rice root responses to endophytic colonization.Putative homologs of genes required for the CSP were analyzed for their putative role in endophytic colonization. Proteomic and suppressive subtractive hybridization (SSH) approaches were also applied, and a comparison of defense‐related processes was carried out by setting up a pathosystem for flooded roots with Xanthomonas oryzae pv. oryzae strain PXO99 (Xoo).All tested genes were expressed in rice roots seedlings but not induced upon Azoarcus sp. inoculation, and the oscyclops and oscastor mutants were not impaired in endophytic colonization. Global approaches highlighted changes in rice metabolic activity and Ca2+‐dependent signaling in roots colonized by endophytes, including some stress proteins. Marker genes for defense responses were induced to a lesser extent by the endophytes than by the pathogen, indicating a more compatible interaction.Our results thus suggest that rice roots respond to endophytic colonization by inducing metabolic shifts and signaling events, for which the CSP is not essential.